SEMANTIC ANALYSIS OF HYPONYMY IN "TINKER BELL AND THE GREAT FAIRY RESCUE" SCRIPT BY J.M. BARRIE - Dewi, Ratna Sari; Maharani, Adinda Putri (PHILOLOGY Journal of English Language and Literature, 2024)
This study aims to find out Semantics Analysis of Hyponymy in “Tinker Bell and The Great Fairy Rescue” Script By J.M Barrie. The results of this study indicate that there are 9 categories of hyponyms and the most dominant category is animals, the total number of hyponyms contained in Semantics Analysis of Hyponymy in “Tinker Bell and The Great Fairy Rescue” Script By J.M Barrie is 38 hyponyms. Script is the pouring of ideas or ideas that contain facts and details in the arrangement of words, both in the composition of the narrative or dialogue, details on the type of shot and decoration information for television shows. it uses uses two methods, the first uses a qualitative method. Qualitative Method is a research method based on philosophy, which is used to research in scientific conditions (experiments) where the researcher as an instrument, technique data collection and analysis that is qualitative emphasizes meaning and this research also uses quantitative methods, is a research method based on philosophy, which is used to examine scientific conditions (experiments) where researchers are instruments, techniques for collecting and analyzing data that are qualitative in nature. more emphasis on meaning.